Understanding mechanisms and the role of differentiation in pathogenesis of Toxoplasma gondii: a review - William J Sullivan Jr; Aaron T Smith; Bradley R Joyce (Memorias do Instituto Oswaldo Cruz, 2009)
Parasite differentiation from proliferating tachyzoites into latent bradyzoites is central to pathogenesis and transmission of the intracellular protozoan pathogen Toxoplasma gondii. The presence of bradyzoite-containing cysts in human hosts and their subsequent rupture can cause life-threatening recrudescence of acute infection in the immunocompromised and cyst formation in other animals contributes to zoonotic transmission and widespread dissemination of the parasite. In this review, we discuss the evidence showing how the clinically relevant process of bradyzoite differentiation is regulated at both transcriptional and post-transcriptional levels. Specific regulatory factors implicated in modulating bradyzoite differentiation include promoter-based cis-elements, epigenetic modifications and protein translation control through eukaryotic initiation factor -2 (eIF2). In addition to a summary of the current state of knowledge in these areas we discuss the pharmacological ramifications and pose some questions for future research.